Patterns of Online Information Seeking and Avoidance about SARS-CoV-2 and COVID-19 - Elena Link; Magdalena Rosset; Anna Freytag (University of Zurich, IKMZ - Department of Communication and Media Research, 2022)
Based on the uncertainty management theory considering different information-based coping strategies that are relevant during health crises, the purpose of the present study is to understand how individuals seek and avoid information during the COVID-19 pandemic. We focus on online information seeking and avoidance because of the high share of people searching for information about the pandemic online and the questionable quality of information about the virus available online. Data for this qualitative exploratory study were collected in semi-structured interviews with 21 participants. Our findings revealed four information-seeking patterns that can be located on a continuum between more active, targeted, and less purposeful acquisitions of information, and three avoidance patterns that are distinguished by different motives to avoid certain information. The findings on specific factors involved in individuals' choices between seeking and avoiding information will help to design better information environments and to identify barriers to the adequate use of information during such crises.